'Duodenibacillus massiliensis' gen. nov., sp. nov., a new species identified in human duodenum. (May 2017) - Mailhe, M.; Ricaboni, D.; Benezech, A.; Lagier, J.-C.; Fournier, P.-E.; Raoult, D.
Abstract: We present here the main characteristics of ' Duodenibacillus massiliensis ' strain Marseille-P2968, which was isolated from a human duodenum liquid sample of a 60-year-old man.